Rapid Detection of Invasive Mycobacterium chimaera Infection by Using a Novel Plasma-Based Next-Generation Sequencing Assay. (4th October 2017) - Nomura, Jim; Rieg, Gunter; Bluestone, Gary; Tsai, Townson; Lai, Andrew; Dryjanski-Yanovsky, Jose; Terashita, Dawn; Bercovici, Sivan; Hong, David; Lee, Brian
Abstract: Background: Mycobacterium chimaera (Mc), a member of the M . A vium complex (MAC), can cause disease months or years after exposure. Mc infection clusters have been linked to contaminated heater-cooler devices (HCDs) used worldwide for temperature control during cardiac surgery. Manifestations of Mc are nonspecific and growth by acid-fast bacilli (AFB) culture typically requires weeks, delaying confirmed diagnosis and possibly contributing to a high case fatality rate (CFR). We compared a novel plasma-based next-generation sequencing (NGS) assay with AFB culture for detection of Mc infection. Methods: Mc cases were identified from February–April 2017 among patients with history of cardiac surgery performed at a Southern California hospital with known Mc exposure risk. A confirmed case was Mc infection identified by AFB culture; a probable case was MAC identified by AFB culture. AFB cultures from blood and biopsy samples were performed at the hospital laboratory. NGS assays on plasma were performed at an outside reference laboratory using an assay developed to detect cell-free pathogen DNA. Human DNA sequences were removed and pathogen reads were aligned against a reference-sequence database with a reportable range of >1, 250 bacteria, fungi, protozoa, and viruses. Organisms present at a significance level above a predefined threshold were reported. Results: Seven cases (6 confirmed and 1 probable) were identified. Six cases had invasive disease; 1 had localized wound infection. AFB cultures were positive in a median of 20 days (range: 6–43 days); whereas speciation to Mc required a median of 41 days (range: 23–92 days) from specimen collection. NGS detected Mc in 5 of 6 cases (83%) with invasive disease in a median of 5 days (range: 2–6 days), and was negative in the single patient with localized infection. Conclusion: This is the first reported detection of Mc by using a plasma-based NGS assay, which identified Mc approximately 15 days sooner than AFB culture positivity and 36 days sooner than speciation from AFB culture. Given widespread exposure to contaminated HCDs and the high CFR after infection, an urgent need exists for rapid, sensitive, noninvasive assays to detect Mc. This NGS assay is a promising rapid diagnostic test for Mc and deserves further investigation. Disclosures: S. Bercovici, Karius, Inc.: Employee, Salary. D. Hong, Karius, Inc.: Employee, Salary. B. Lee, Karius, Inc.: Employee, Salary